Being young with HIV is a higher risk for non-adherence to ART in Chihuahua, Mexico - Maria Guadalupe Staines-Orozco; Itzel Patricia Miranda-Quezada; María Sandra Compeán-Dardón; Diana Pérez-Salgado; Luis Ortiz-Hernandez (Social Medicine Publication Group, 2023)
Introduction. Mortality due to HIV/AIDS in Mexico is 3.62 per 100,000 inhabitants. Most research on ART adherence in the Mexican population has considered only people with HIV/AIDS living in Mexico City. Due to the different social characteristics (e.g. conservatism) in other states of the Mexican Republic, it is to be expected that there are different factors related to ART adherence. Objective. To analyze the association of individual characteristics, health care institutions, and antiretroviral treatment with adherence in people with HIV residing in Chihuahua. Results. The sample population (n=211) had a mean age of 37.6 years (±10.3 SD), with a minimum of 18 years and a maximum of 67 years. The first multivariate analysis showed that the younger the age, the greater the risk of nonadherence. The second multivariate analysis showed the same pattern according to the age of the participants; in addition, those who noted increased body fat had a higher risk of nonadherence to ART. Conclusion. Health professionals treating people living with HIV should pay special attention to young people and those with increased body fat to reduce the risk of low adherence.